2016
DOI: 10.1107/s2053230x16012796
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure ofHalobacterium salinarumhalorhodopsin with a partially depopulated primary chloride-binding site

Abstract: The transmembrane pump halorhodopsin in halophilic archaea translocates chloride ions from the extracellular to the cytoplasmic side upon illumination. In the ground state a tightly bound chloride ion occupies the primary chloride-binding site (CBS I) close to the protonated Schiff base that links the retinal chromophore to the protein. The light-triggered trans-cis isomerization of retinal causes structural changes in the protein associated with movement of the chloride ion. In reverse, chemical depletion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Using carefully performed B-factor analyses on the basis of normalized values, inter alia, it was found that large movements of two helices (E and F) during the photocycle are essentially unrestrained by packing effects and that the crystal lattice is not disrupted . Later this research was extended …”
Section: Identifying and Interpreting Rigidity Flexibility And Dynami...mentioning
confidence: 94%
See 1 more Smart Citation
“…Using carefully performed B-factor analyses on the basis of normalized values, inter alia, it was found that large movements of two helices (E and F) during the photocycle are essentially unrestrained by packing effects and that the crystal lattice is not disrupted . Later this research was extended …”
Section: Identifying and Interpreting Rigidity Flexibility And Dynami...mentioning
confidence: 94%
“…102 Later this research was extended. 103 In a different recent contribution, J. Li and co-workers utilized B-factors in a very different way. 68 They stressed the importance of distinguishing between true protein interactions and crystal packing contacts, which is of obvious significance when developing reliable structural bioinformatics procedures.…”
Section: Identifying and Interpreting Rigidity Flexibility And Dynami...mentioning
confidence: 99%
“…Two crystal structures of NM-R3 in the dark state have been published, and two chloride ions are found; Cl-1 lies close to the Schiff base, and Cl-2 lies in an extracellular surface pocket (11,12). The network of bonds between chloride ions and highly ordered water molecules in NM-R3 is different from that of other chloride-pumping rhodopsins (4,14,15). Overlaying NM-R3 and NpHR with secondary-structure matching (SSM) (16) shows that the proteins share 17% sequence identity, and a core region of 202 C atoms gives a root mean square deviation (RMSD) of 1.79 Å.…”
Section: Introductionmentioning
confidence: 99%
“…We considered that the observed changes could be related to the “bent structure” at the C‐terminus of helix E, where T164 and S165 are located. Despite their low sequence similarities, the “bent structure” is conserved in most microbial rhodopsins, including proton pumps , sensory rhodopsins and halorhodopsins , suggesting that the structure may be functionally important in different types of microbial rhodopsins (Figure ). On closer inspection of amino acid sequences in this region, these microbial rhodopsins seem to apply different strategies to attain a “bent structure”.…”
Section: Discussionmentioning
confidence: 99%